2019
DOI: 10.1007/s40962-018-00302-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vacuum on the Mechanical Properties of Die Cast Aluminum AlSi9Cu3(Fe) Alloy

Abstract: High pressure die casting (HPDC) is a widely used casting technology for product that is made of light metal such as aluminum alloy. During die casting process the molten metal is injected into a mold at high speed and solidify under high pressure. The amount of porosity in the cast part is an important question. Lots of technologies have been developed to minimize porosities, for example, vacuum-assisted high pressure die casting process (VPDC). In this paper, AlSi9Cu3(Fe) aluminum alloy castings were produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Wang et al [6] found through their research on fatigue fracture of die-casting parts that 98.5% of fatigue crack sources in die-casting alloys originate from internal pores in the castings; Koch et al [7] have shown that the fatigue crack source of die-casting alloys is located at the edge of the void defect near the center of the specimen, and the crack grows outward during tension. After studying the relationship between internal defects and the casting performance of diecasting parts, Szalva et al [8][9] found that the differences in mechanical properties of die-casting parts are caused by different areas of high concentrations of gas pores in the specimens, and gas shrinkage is the main factor affecting the elongation of die-casting alloy. Easton et al [10] found that tensile fracture cracks are generated along grain boundaries, and they mostly occur near the surface defect zone of the casting.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [6] found through their research on fatigue fracture of die-casting parts that 98.5% of fatigue crack sources in die-casting alloys originate from internal pores in the castings; Koch et al [7] have shown that the fatigue crack source of die-casting alloys is located at the edge of the void defect near the center of the specimen, and the crack grows outward during tension. After studying the relationship between internal defects and the casting performance of diecasting parts, Szalva et al [8][9] found that the differences in mechanical properties of die-casting parts are caused by different areas of high concentrations of gas pores in the specimens, and gas shrinkage is the main factor affecting the elongation of die-casting alloy. Easton et al [10] found that tensile fracture cracks are generated along grain boundaries, and they mostly occur near the surface defect zone of the casting.…”
Section: Introductionmentioning
confidence: 99%
“…The change in crystallization volume and the degree of gas porosity and air entrapment can be compensated for with a variety of die-casting processes (e.g., melt treatment, postpressure, post-compression). With these methods, porosity can be reduced to 0.2-0.5% in quality casting [3][4][5]. This amount of porosity is unacceptable where gas permeability is not allowed.…”
Section: Introduction Backgroundmentioning
confidence: 99%